Influence of temperature on continuous high gravity brewing with yeasts immobilized on spent grains - Dragone, Giuliano (2008)
Flavor compounds’ formation and fermentative parameters of continuous high gravity brewing with yeasts immobilized on spent grains were evaluated at three different temperatures (7, 10 and 15 °C). The assays were performed in a bubble column reactor at constant dilution rate (0.05 h−1) and total gas flow rate (240 ml/min of CO2 and 10 ml/min of air), with high-gravity all-malt wort (15°Plato). The results revealed that as the fermentation temperature was increased from 7 to 15 °C, the apparent and real degrees of fermentation, rate of extract consumption, ethanol volumetric productivity and consumption of free amino nitrogen (FAN) increased. In addition, beer produced at 15 °C presented a higher alcohols to esters ratio (2.2–2.4:1) similar to the optimum values described in the literature. It was thus concluded that primary high-gravity (15°Plato) all-malt wort fermentation by continuous process with yeasts immobilized on spent grains, can be carried out with a good performance at 15 °C.